TRPC3 positively regulates reactive oxygen species driving maladaptive cardiac remodeling - Kitajima, Naoyuki (2016)
Fil: Kitajima, Naoyuki. National Institute for Physiological Sciences. Division of Cardiocirculatory Signaling. Okazaki Institute for Integrative Bioscience; Japón